Arctic temperature effects on the mechanical properties and failure modes of photopolymer resin for sandwich composite core' materials - Zackery Nieto; Alejandra G. Castellanos (Results in Engineering)
The increased marine activity in the Arctic Circle presents significant challenges for naval structures operating in extreme conditions, such as temperatures as low as -60°C (Arctic temperature, AT). This study uniquely investigates the potential of Formlabs' “Durable resin” as a core material for sandwich composites. It focuses explicitly on its mechanical response under these extreme Arctic conditions, a largely unexplored area in current materials research. Durable resin's quasi-static tensile, flexural, and compressive behaviors were tested at both room temperature (RT) and AT. Finite element models were developed to explain observed failure mechanisms. At AT, the resin showed isotropic behavior with notable improvements, including a 318% increase in tensile modulus, 322% rise in ultimate tensile strength, 450% increase in flexural modulus, and 460% improvement in compressive modulus, though strain at failure decreased. Failure modes varied by temperature: tensile and flexural fractures consistently occurred at the midsection, while compressive samples at AT failed via axial splitting, compared to barreling at RT. This study's findings contribute to the foundational understanding needed to develop materials that endure extreme Arctic environments, underscoring the promise of Durable resin for Arctic exploration despite its reduced ductility under AT conditions.